MEMBENTUK KARAKTER ANAK DIDIK MELALUI PASRAMAN (SEBUAH SOLUSI SISTEM PENDIDIKAN NASIONAL) - Sentana Putra, Kadek Dwi (Institut Hindu Dharma Negeri Denpasar, 2020)
Education is a very important aspect in the life of each individual, because through education human will get knowledge that can be used in their life. Education can be obtained in various ways, one of them is through the school, where the character of each child is expected to be formed since an early childhood. However, currently there are phenomena which indicate the presence of moral degradation exhibited by school-age children, such as the number of student fights and deeds other improperly. Seeing this phenomenon, arises the question